Método de armadilha melhorado para a coleta de Hymenoptera, especialmente de vespas sociais (Vespidae: Polistinae) - Noll, Fernando B. [UNESP] (2009)
In this work, an alternative method for the capture of neotropical social wasps is described, which may supplement or replace the procedures commonly used in wasp surveys. The method was tested in a seasonal semideciduous forest in the northwest of São Paulo State, collecting a larger number of species and a greater abundance of social wasps and of other Hymenoptera than other methods also used in the same area, namely Malaise traps, bottle traps and meat baits. The proposed method was adapted from Wille (1962) who used an attractive solution based on water and honey for bee attraction. In here, the attractive solution was based on water, salt and crystal sugar, and was effective in attracting bees and solitary wasps, but mainly social wasps, which is the group of interest for this report.